In vitro analysis of nucleic acid recognition in B lymphocytes - Ziegler, Saskia; Bekeredjian-Ding, Isabelle (Innate DNA and RNA recognition, 2014)
In contrast to murine B cells, Toll-like receptor (TLR) expression in human B cells is mainly restricted to endosomally localized TLR7 and -9, receptors for RNA and DNA, respectively. Most importantly, B lymphocytes lack classical phagocytic receptors and instead internalize antigen only via the B cell receptor (BCR), a surface immunoglobulin specific for a defined antigen. BCR ligation triggers internalization of particulate antigens and physically associated molecules among them bacterial DNA or RNA. Thereby, this process provides access to endosomal nucleic acid-sensing TLRs. Co-stimulation of BCR and TLR ultimately leads to T cell-independent B cell activation. Here, we explain how this process can be experimentally mimicked in human peripheral blood B cells, e.g., using a microsphere-based system that promotes uptake of nucleic acid-based TLR ligands via BCR engagement.